The European Union a stepping stone to further integration or rather a Eurocentric fortress? - Kraushaar, Maren (Politikon: The IAPSS Journal of Political Science, 2006)
The European Union a stepping stone to further integration or rather a Eurocentric fortress? Still with the memory of the destructive national power of the Second World War, the main initiators of the European integration stirred this project with the objective of preventing further conflicts through economic integration. Closer economic ties, spilling over to more countries and more policy areas lead to the development of an ever closer union which has become a powerful actor in international affairs. This essay will explore the question to what extent the European Union can be characterized as Eurocentric regionalism, rather focused on internal integration and enforcing outside borders than on global understanding. In order to shed light on this question several policy areas will be analysed, such as the European aid and trade policy, as well as the agricultural policy as these are areas where the European Union is directly confronted with external politics and international interests.